Perpetrator characteristics and blame attributions in a stranger rape situation - Leif A. Strömwall (European Journal of Psychology Applied to Legal Context, 2014)
Both real-life events and research show that rape victims are sometimes blamed for their victimization. The effect of perpetrator characteristics on victim blaming has rarely been studied. In an experiment using a community sample (N = 161), we investigated the effect of the perpetrator's previous conviction and age, as well as participants' gender and belief in a just world (BJW) on blame attributions using a vignette methodology. It was predicted that less victim blame and more perpetrator blame would be attributed when the perpetrator had a previous conviction. Results showed that level of BJW was associated with victim blame (positively) and perpetrator blame (negatively). Men blamed the victim more and women blamed the victim less when the perpetrator had a previous conviction. Women blamed the perpetrator more and men less when the perpetrator had a previous conviction. Hence, gender is an important factor in explaining variation in blame attributions.